Periodismo digital y su incidencia en las relaciones interpersonales de los habitantes del Recinto San Miguel de Jauneche del cantón Palenque, año 2022 - Muñoz Chiriguaya, Kevin Armando (2022)
This paper describes and analyzes the behavior of interpersonal relationships, delving into communication and technological innovation. Different conceptions about social networks are presented, with their characteristics, advantages and disadvantages in postmodern society. The mode of interactive subject-subject communication as one of the contemporary relational forms. Controversial and critical positions are presented on the modes of virtual relationships, as an expression of the fragility of human bonds. The purpose of this research is to improve interpersonal relationships and their impact on internal customer service, due to the importance of customer satisfaction for the future of the institution.